Pemberdayaan Masyarakat Melalui Pelatihan Konten Kreatif Dalam Mempromosikan Desa Wisata Muncar Kecamatan Susukan - Yusuf, Ichwan Akhirudin (Jurnal Bina Desa, 2025)
In the current era of digitalization ofsocialmedia, creative contentthatis published or uploaded can play an important role in promoting and attracting consumer interest, this can provide many benefits for the localcommunity. The service carried out by the UNNES GIAT 8 Team can provide contributions and objectives, namely (1) to empower the community in creative content training for Pokdarwis and young people. (2) to develop creative content and promote the Muncar tourist village. The objects ofthisservice are young people and Pokdarwis, totaling 10 people. The method used in implementing this service is training and mentoring. This implementation has been carried out twice, namely on March 1 and March 25 2024, by carrying out direct outreach atthe Muncar village hall. By empowering the community throughcreative contenttraining, results were obtained thatshowed that there were real changes after being given training and assistance in creating creative content. The creativity of young people and community groups hasincreased to convey content ideas and try to promote themon socialmedia.